PERSEPSI ULAMA, TOKOH ORMAS ISLAM DAN AKADEMISI DI PROVINSI BANTEN TERHADAP BAURAN PEMASARAN PERBANKAN SYARIAH DAN KESESUAIAN PRAKTIK PERBANKAN SYARIAH DENGAN PRINSIP-PRINSIP SYARIAH - Rosiana, Rita; Indrinana, Ina; Badina, Tenny; Najib, Mohamad Ainun; Atiah, Isti Nuzulul (ALQALAM, 2017)
Many factors that affect a person's interest in doing something, in this case the author intended is the selection of interest in choosing the community of Islamic banking services. A person's interest in choosing a product is influenced by his perception and knowledge of the product. This study aims to know and analyze the perceptions of the scholars, the leaders of  Islamic organizations and academics of sharia banking and its influence on the growth of Islamic banking in Banten. Teknik data collection used in this research is convenient sampling method. Convenient technique is used because the number of scholars in Banten is very much and the researchers chose the board of MUI of Banten Province as the representative of the ulama in Banten. The type of data used in this study is primary data collected directly by researchers from the field. The data source used in this research is field research (field data) and library research (library data) .The data collection techniques used in this study survey through questionnaires and interviews with the respondents. Based on the results of questionnaires research on 3 groups of Respondents: MUI (30 respondents), Academics (30 respondents), and Islamic Organizations (30 respondents) can be concluded that respondents from academic groups agree on the suitability of the practice and marketing mix of sharia banking with average value 3.77, while respondents from the MUI group and Islamic organizations strongly agree on the suitability of the practice and marketing mix of sharia banking with an average value of 4.11 and 4.35.